Static and sustained loading behavior of a basalt FRP shell–concrete composite bridge deck: An experimental and numerical study. (1st March 2021) - Peng, Zheqi; Wang, Xin; Ding, Lining; Yang, Yizhi; Wu, Zhishen; Zhu, Zhongguo
Highlights: An optimized basalt FRP-concrete composite bridge deck was proposed and studied. The new bridge deck exhibited decent behavior under static and sustained loads. The numerical results fitted well with experimental ones for both loads. Abstract: The fiber reinforced polymer (FRP)-concrete composite bridge deck is expected to be a competitive alternative to the reinforced concrete bridge deck owing to its great durability, low weight, and high loading efficacy. Based on previous studies, an optimized basalt FRP shell (BFRP)–concrete composite bridge deck was investigated experimentally and numerically in this study. Through the construction simulation test, the optimized BFRP shell was proved to be a qualified formwork with a 30.9% lower midspan deflection than the BFRP shell of previous studies and was lower than 1/800 of the net span. In the static test, the load capacities of deck specimens with depths of 200 mm and 180 mm reached 470 kN and 340 kN, respectively, with residual deflections lower than 7 mm. Meanwhile, the deck showed decent collaborative behavior, without visible interfacial debonding or slippage during the static test. Compared with the previously studied bridge deck, the bridge deck of the current study can achieve a higher short-term cost performance. After 175 days of three-point flexural sustained loading, the additional midspan deflections were 0.3 mm, 0.37 mm, and 0.46 mm, for load levels of 0.2, 0.25, and 0.3, respectively, which were less than 7% of their instantaneous elastic deflections. The finite element (FE) model was established using the Bailey-Norton model for the creep of the FRP and Bazant's B-3 model for the creep of the concrete. The FE results were in good agreement with the experimental results, both in short- and long-term scenarios. Using numerical simulation with a load duration of 50 years, the allowable load level of this bridge deck reached 0.4, which meets the criteria for creep deflection in the ACI standard.